Bioactive Herbal Medicine Use for Eye Sight: A Meta Analysis - Amle, Vandana Sonaji; Rathod, Dharmaraj Arjun; E., Dr. Keshamma; Kumar, Vijender; Kumar, Roshan; Saha, Purabi (Journal for Research in Applied Sciences and Biotechnology, 2022)
The use of chemical medications to treat eye conditions in a way that avoids causing harm is still a work in progress for modern medicine. Herbal remedies, however, may be able to solve the problems that conventional pharmaceuticals have. Given their efficacy, lack of adverse effects, and inexpensive cost, there have been extensive efforts to discover novel medicinal plants from various locations. Several plant species have been promoted in Traditional Indian Medicine for their ophthalmic effects, and it is estimated that around 200 plants worldwide have been documented to support therapy of eye problems. This review seeks to shed light on the history of using various plants to treat eye illnesses, the advantages and disadvantages of those approaches, and the advantages of modern medicine over those of the plants themselves. Based on the findings of this review, the most effective Ayurvedic preparations may be created by combining traditional knowledge with modern techniques and polymers.